Silver oxide / tungsten trioxide hollow microsphere composite material and preparation method and application thereof
The silver oxide/tungsten trioxide hollow microsphere composite synthesized by hydrothermal method as a sensitive layer material solves the problems of high working temperature, slow response recovery and low sensitivity of existing WO3-based sensors, and achieves high hydrogen sulfide gas Sensitivity, fast response detection.
Patent Information
- Application Number
- CN202411512392.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-11
AI Technical Summary
The existing WO3-based gas sensors have problems such as high operating temperature, slow response recovery, and low sensitivity, making it difficult to effectively monitor low concentrations of hydrogen sulfide gas.
The silver oxide/tungsten trioxide (Ag2O/WO3) hollow microsphere composite was synthesized by hydrothermal method, and a bionic olfactory sensor was prepared as a sensitive layer material to achieve continuous detection of 0.05-50ppm hydrogen sulfide gas.
High sensitivity detection of hydrogen sulfide gas at low temperature of 60°C is achieved, with a response time of 15 s and a detection limit as low as 50 ppb, with fast response, low detection lower limit, high selectivity and reliable stability.
Smart Images

Figure HDA0005105795870000011 
Figure HDA0005105795870000012 
Figure HDA0005105795870000021
Abstract
Description
Technical Field
[0001] The invention relates to a silver oxide / tungsten trioxide hollow microsphere composite material and a preparation method and application thereof, belonging to the field of gas sensors. Background Art
[0002] All living things are equipped with biological sensory systems such as light, sound, and smell to monitor and adapt to the environment. For humans, we also use artificial sensors to enhance our natural ability to perceive the world and improve our living conditions. Hydrogen sulfide (H2S) is a toxic, harmful, flammable and explosive acidic gas with the smell of rotten eggs. It can damage human health and is one of the main causes of air pollution. According to the national standard formulated by the Ministry of Ecology and Environment of China (GB 14761.1-14761.7-93), the threshold limit for the unorganized emission of sulfides in air pollutants is 0.50mg / m 3 (330ppb). The Scientific Advisory Committee on Toxic Air Pollutants recommends that the acceptable limit range of H2S in the environment is 20-100ppb. In addition, especially in the power industry, H2S, as the main decomposition product of the insulating gas sulfur hexafluoride (SF6), is an important indicator for maintaining the safe and stable operation of the power industry, whether it reflects the amount of internal discharge or determines whether the fault involves solid insulating materials. Therefore, it is crucial to monitor H2S in a timely manner to avoid harm.
[0003] At present, there are various methods for H2S gas detection. Driven by the emerging 5G and Internet of Things (IoT) technologies, MOS-based gas sensors have attracted much attention due to their fast response speed, low price and high sensitivity. The selection of sensitive layer materials is a key technology for the development of gas sensors. At present, sensitive materials for H2S gas detection include ZnO, CuO, NiO, SnO2, In2O3 and WO3. As a typical n-type semiconductor material, WO3 has a band gap energy of 2.6-3.2eV and its band structure is similar to that of TiO. When doped with alkali metals, WO3 can form tungsten bronze with photoelectric properties such as electrochromism. In the field of gas sensors, since the WO3 crystal structure is similar to defective tremolite (ReO3), its lattice structure forms different lattice types and undergoes various structural transitions under different temperature conditions. This is conducive to increasing oxygen vacancies and providing more adsorption sites, making it one of the most ideal sensitive materials. In recent years, WO3 has performed well in the presence of toxic and harmful gases, but it still has problems such as high operating temperature, slow response recovery, and low sensitivity, which poses a huge challenge to energy consumption, component life and safety. Therefore, it is necessary to continue to develop new materials based on WO3, optimize its gas-sensitive properties, and improve its high operating temperature, slow response recovery, and low sensitivity. Summary of the invention
[0004] In order to overcome the shortcomings in the production of existing bionic olfactory gas sensors, the present invention provides a silver oxide / tungsten trioxide hollow microsphere composite material and its preparation method and application, and specifically relates to the application of a silver oxide / tungsten trioxide hollow microsphere composite material as a hydrogen sulfide gas sensitive material. The present invention adopts a simple hydrothermal method to synthesize a silver oxide / tungsten trioxide (Ag2O / WO3) hollow microsphere composite material. The bionic olfactory sensor prepared by using the composite material as a sensitive layer material can continuously cycle and detect 0.05-50ppm of hydrogen sulfide gas at a low temperature of 60°C, and has ultra-high sensitivity, fast response capability, low detection limit, high selectivity and reliable stability.
[0005] The first object of the present invention is to provide a silver oxide / tungsten trioxide hollow microsphere composite material, the microscopic morphology of which is that silver is attached and grown on the surface of tungsten trioxide hollow microspheres in the form of silver oxide nanoparticles, wherein:
[0006] The silver oxide has a cubic crystal structure, the tungsten trioxide has a monoclinic crystal structure, and the interface region formed by the contact between the silver oxide and the tungsten trioxide is a pn heterojunction.
[0007] Furthermore, the raw material required for preparing silver oxide (Ag2O) is silver nitrate (AgNO3), and the raw material required for preparing tungsten trioxide (WO3) is tungsten hexachloride (WCl6), wherein the molar ratio of silver nitrate to tungsten hexachloride is 30% to 50%.
[0008] The second object of the present invention is to provide a method for preparing a silver oxide / tungsten trioxide hollow microsphere composite material: tungsten hexachloride is added to glacial acetic acid, stirred evenly, and then subjected to hydrothermal reaction, cooled after the reaction is completed, centrifugally washed, dried, and then calcined to obtain a tungsten trioxide solid powder; the tungsten trioxide powder obtained above is added to anhydrous ethanol aqueous solution, stirred evenly, and then silver nitrate is added, the stirring is continued evenly, and then subjected to hydrothermal reaction, cooled after the reaction is completed, and centrifugally washed and dried to obtain a silver oxide / tungsten trioxide hollow microsphere composite material.
[0009] In the method of the present invention, the molar volume ratio of the tungsten chloride to the glacial acetic acid is 1 mmol:35 mL.
[0010] In the method of the present invention, the mass volume ratio of the tungsten trioxide to the mixed solution of anhydrous ethanol and deionized water is 0.20g:30mL, wherein the volume ratio of deionized water to anhydrous ethanol in the anhydrous ethanol aqueous solution is 1:1.
[0011] In the method of the present invention, the first stirring condition is stirring at 2000-4000 rpm for 25-35 min.
[0012] In the method of the present invention, the second stirring condition is stirring at 2000-4000 rpm for 25-35 min.
[0013] In the method of the present invention, the continued stirring condition is stirring at 2000-4000 rpm for 50-70 min.
[0014] The stirring operations involved in the present invention are all carried out in a stirring device provided by the prior art, preferably a magnetic stirrer.
[0015] In the method of the present invention, the first hydrothermal reaction condition is to react at 170-190° C. for 11-13 hours.
[0016] In the method of the present invention, the second hydrothermal reaction condition is to react at 170-190° C. for 4-6 hours.
[0017] In the method of the present invention, the hydrothermal reaction is carried out in a high-pressure reactor with a volume of 50 mL and a polytetrafluoroethylene lining.
[0018] In the method of the present invention, the hydrothermal reaction is carried out in a heating device provided by the prior art, preferably an oven.
[0019] In the method of the present invention, the first centrifugation condition is centrifugation at 2000-4000 r / min for 2000-4000 min.
[0020] In the method of the present invention, the second centrifugation condition is centrifugation at 2000-4000 r / min for 2000-4000 min.
[0021] In the method of the present invention, the washing conditions are to first wash with deionized water for 3 to 4 times, and then wash with anhydrous ethanol for 3 to 4 times.
[0022] In the method of the present invention, the calcination conditions are calcination at 490-510° C. for 50-70 min, wherein the heating rate is 2° C. / min.
[0023] Furthermore, the calcination operation is carried out in a muffle furnace.
[0024] In the method of the present invention, the drying conditions are drying at 60-70° C. in a constant temperature vacuum drying oven for 8-12 hours, and the vacuum degree is maintained at 700-800 Pa.
[0025] The third object of the present invention is to provide the application of the silver oxide / tungsten trioxide hollow microsphere composite material obtained as a hydrogen sulfide gas sensitive material.
[0026] A fourth object of the present invention is to provide a bionic olfactory gas sensor.
[0027] Furthermore, the hydrogen sulfide gas sensitive layer material of the sensor is the silver oxide / tungsten trioxide hollow microsphere composite material prepared by the above method.
[0028] Furthermore, the bionic olfactory sensor can detect 0.05-50 ppm hydrogen sulfide gas in a continuous cycle at a low temperature of 60°C, with a sensitivity of 207.12, 10 ppm, a response time of 15 s, and a detection limit of 50 ppb.
[0029] Furthermore, the sensitivity calculation formula is Ra / Rg, wherein Ra is the stable resistance of the sensitive layer in air, and Rg is the stable resistance of the sensitive layer in H2S gas.
[0030] Beneficial effects of the present invention:
[0031] 1. The present invention prepares a three-dimensional graded hollow microsphere Ag2O / WO3 pn heterojunction material by a simple hydrothermal method, which reduces the preparation cost of the sensitive layer material of the bionic olfactory gas sensor and can realize large-scale production.
[0032] 2. The composite of Ag2O is more conducive to the improvement of the gas-sensing performance of the sensitive layer material of the bionic olfactory gas sensor. The response value of the Ag2O / WO3 sensor to 10ppm H2S at 60°C is as high as 207.12, and it can continuously detect 0.05-50ppm H2S gas, with a detection limit as low as 50ppb. The present invention provides a feasible strategy for realizing high-performance gas-sensitive materials for efficient detection of low-concentration harmful gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The crystal structure diagram and phase purity diagram of the pure phase WO3 and Ag2O / WO3 hollow microsphere composite materials obtained in Example 2.
[0034] Figure 2 SEM images of WO3 (a) and Ag2O / WO3 hollow microsphere composite material (b) obtained in Example 2.
[0035] Figure 3 (a) is the TEM image of WO3 obtained in Example 2; Figure 3 (b) and Figure 3 (c) is a TEM image of the Ag2O / WO3 hollow microsphere composite material obtained in Example 2; Figure 3 (d) is the HRTEM image of the Ag2O / WO3 hollow microsphere composite material obtained in Example 2.
[0036] Figure 4 This is the response-temperature curve of the WO3 and Ag2O / WO3 hollow microsphere composite materials obtained in Example 2.
[0037] Figure 5 Response / recovery curves of WO3 and Ag2O / WO3 hollow microsphere composites obtained in Example 2 to 10 ppm H2S gas at 60°C (a) and 70°C (b).
[0038] Figure 6 This is a continuous response diagram of the Ag2O / WO3 hollow microsphere composite material obtained in Example 2 to different concentrations of H2S gas at the optimal working temperature of 60°C.
[0039] Figure 7 This is a selectivity test diagram of the WO3 and Ag2O / WO3 hollow microsphere composite materials obtained in Example 2.
[0040] Figure 8 (a) is a curve graph of 10 consecutive response / recovery experiments of the Ag2O / WO3 hollow microspheres obtained in Example 2 exposed to 10 ppm H2S gas at 60°C on the 20th day; Figure 8 (b) is a graph showing the changes in the response values of the WO3 and Ag2O / WO3 hollow microsphere composite materials obtained in Example 2 within 30 days and the resistance value (Ra) of the Ag2O / WO3 hollow microsphere composite materials.
[0041] Fig. 9 (a) is a schematic diagram of the H2S gas sensing mechanism of the Ag2O / WO3 hollow microsphere composite material obtained in Example 2; Fig. 9 (b) is the energy band structure diagram of WO3 and Ag2O / WO3 hollow microsphere composite materials obtained in Example 2. DETAILED DESCRIPTION
[0042] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0043] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0044] Example 1
[0045] A method for preparing a silver oxide / tungsten trioxide hollow microsphere composite material comprises the following steps:
[0046] Step 1: Add 1 mmol of tungsten hexachloride (WCl6, purchased from Shandong Xiya Chemical Technology Co., Ltd.) to 35 mL of glacial acetic acid (C2H4O2, purchased from Tianjin Beilian Fine Chemical Development Co., Ltd.), stir with a magnetic stirrer at 3000 rpm for 30 min to obtain a mixed solution, pour it into a high-pressure reactor (volume of 50 mL) lined with polytetrafluoroethylene, transfer it to an oven for hydrothermal reaction at 180°C for 12 h to obtain a mixture, and naturally cool to room temperature after the reaction is completed. The obtained mixture is centrifuged and washed 3 times with water and anhydrous ethanol (C2H5OH, purchased from Tianjin Fuyu Fine Chemical Co., Ltd.), dried at 60°C for 8 h, and then the dried precipitate is placed in a 500°C muffle furnace and calcined for 1 h, with a heating rate of 2°C / min to obtain tungsten trioxide (WO3) solid powder;
[0047] Step 2: Add 0.2g WO3 obtained in step 1 to a mixed solution of 30mL anhydrous ethanol and deionized water (the volume ratio of deionized water and anhydrous ethanol is 1:1, and 15mL of each is taken), stir with a magnetic stirrer at 3000rpm for 30min to obtain a mixed solution, then add 0.044g silver nitrate (AgNO3, purchased from Tianjin Fuchen Chemical Reagent Factory) to the mixed solution, continue to stir at 3000rpm for 60min to mix the solution evenly, then pour it into a high-pressure reactor lined with polytetrafluoroethylene, transfer it to a 180℃ oven for heating and hydrothermal reaction for 5h to obtain a mixture, and naturally cool to room temperature after the reaction is completed. The obtained mixture is centrifuged and washed 3 times with water and anhydrous ethanol respectively, and dried at 60℃ for 8h to obtain a silver oxide / tungsten trioxide (Ag2O / WO3) hollow microsphere composite material.
[0048] Example 2
[0049] A method for preparing a silver oxide / tungsten trioxide hollow microsphere composite material comprises the following steps:
[0050] Step 1: Add 1 mmol of WCl6 to 35 mL of glacial acetic acid, stir with a magnetic stirrer at 3000 rpm for 30 min to obtain a mixed solution, pour it into a high-pressure reactor (volume of 50 mL) lined with polytetrafluoroethylene, transfer it to an oven for hydrothermal reaction at 180°C for 12 h to obtain a mixture, and naturally cool to room temperature after the reaction is completed. The obtained mixture is centrifuged and washed with water and anhydrous ethanol for 3 times, respectively, and dried at 60°C for 8 h. Then, the dried precipitate is placed in a 500°C muffle furnace and calcined for 1 h, with a heating rate of 2°C / min to obtain WO3 solid powder;
[0051] Step 2: Add 0.20 g WO3 obtained in step 1 to a mixed solution of 30 mL of anhydrous ethanol and deionized water (the volume ratio of deionized water and anhydrous ethanol is 1:1, and 15 mL of each is taken), stir with a magnetic stirrer at 3000 rpm for 30 min to obtain a mixed solution, then add 0.0586 g AgNO3 to the mixed solution, continue stirring at 3000 rpm for 60 min to mix the solution evenly, and then pour it into a high-pressure reactor (volume of 50 mL) lined with polytetrafluoroethylene, transfer it to a 180°C oven for heating for hydrothermal reaction for 5 h to obtain a mixture, and naturally cool to room temperature after the reaction is completed. The obtained mixture is centrifuged and washed 3 times with water and anhydrous ethanol respectively, and dried at 60°C for 8 h to obtain an Ag2O / WO3 hollow microsphere composite material.
[0052] Example 3
[0053] A method for preparing a silver oxide / tungsten trioxide hollow microsphere composite material comprises the following steps:
[0054] Step 1: Add 1 mmol of WCl6 to 35 mL of glacial acetic acid, stir with a magnetic stirrer at 3000 rpm for 30 min to obtain a mixed solution, pour it into a high-pressure reactor (volume of 50 mL) lined with polytetrafluoroethylene, transfer it to an oven for hydrothermal reaction at 180°C for 12 h to obtain a mixture, and naturally cool to room temperature after the reaction is completed. The obtained mixture is centrifuged and washed with water and anhydrous ethanol for 3 times, respectively, and dried at 60°C for 8 h. Then, the dried precipitate is placed in a 500°C muffle furnace and calcined for 1 h, with a heating rate of 2°C / min to obtain WO3 solid powder;
[0055] Step 2: Add 0.20g WO3 obtained in step 1 to a mixed solution of 30mL anhydrous ethanol and deionized water (the volume ratio of deionized water and anhydrous ethanol is 1:1, and 15mL of each is taken), stir with a magnetic stirrer at 3000rpm for 30min to obtain a mixed solution, then add 0.0733g AgNO3 to the mixed solution, continue stirring at 3000rpm for 60min to mix the solution evenly, and then pour it into a high-pressure reactor (volume of 50mL) lined with polytetrafluoroethylene, transfer it to a 180℃ oven for heating for hydrothermal reaction for 5h to obtain a mixture, and naturally cool to room temperature after the reaction is completed. The obtained mixture is centrifuged and washed 3 times with water and anhydrous ethanol respectively, and dried at 60℃ for 8h to obtain a hollow microsphere composite gas-sensitive material.
[0056] Figure 1The crystal structure diagram and phase purity diagram of the pure phase WO3 and Ag2O / WO3 hollow microsphere composite materials obtained in Example 2. X-ray diffraction (XRD) was used to analyze the crystal structure and phase purity of pure WO3 and Ag2O / WO3. It can be seen that the diffraction peaks of all samples are consistent with the monoclinic WO3 standard card JCPDS No.72-0677. Specifically, the diffraction peaks are located at 23.109°, 23.579°, 24.349°, 33.252°, 34.151°, 49.893° and 55.894°, which belong to the (002), (020), (200), (022), (202), (400) and (420) crystal planes of monoclinic WO3, respectively; the diffraction peaks of WO3 and Ag2O / WO3 hollow microsphere composites are almost the same, and no obvious other stray peaks are observed, indicating that the synthesized samples are of high purity.
[0057] This may be because, on the one hand, Ag2O exists in the form of low-dimensional nanoparticles with a small volume, and no obvious silver oxide diffraction peak can be observed even at a high addition amount of 50% silver nitrate (Example 3); on the other hand, the addition of the Ag source does not change the lattice structure of the WO3 nanomaterial. However, a careful observation shows that with the increase of the Ag source content, the diffraction peak at 32.853° gradually increases, which corresponds to the (111) crystal plane of the cubic structure Ag2O (JCPDS NO.75-15332). In addition, when the addition amount of AgNO3 is 0.0586g (Example 2), Ag2O / WO3 has an obvious diffraction peak at 38.116°, and the diffraction peak here represents the (200) crystal plane of the cubic structure Ag2O. Therefore, silver exists in the form of Ag2O in the composite material.
[0058] Figure 2 The SEM spectra of WO3 (a) and Ag2O / WO3 hollow microsphere composite material (b) obtained in Example 2 show that the materials are all three-dimensional hierarchical hollow microsphere structures self-assembled from nanoparticles; the surface of WO3 is relatively smooth, and the Ag in Ag2O / WO3 grows on the surface of WO3 in the form of Ag2O nanoparticles (NPs), and with the addition of silver source, the surface of the material is slightly rough and has cracks. The rough surface is conducive to increasing the chance of H2S gas contacting the surface of the material, and the cracks are conducive to the diffusion reaction of the gas into the depth of the material, promoting the reaction of adsorbed oxygen ions and H2S gas, and improving the gas-sensitive performance of the material. After measurement, it is known that the diameter of the WO3 sphere is about 1μm, and the diameter of the Ag2O / WO3 composite is about 1.7μm. The enlargement of the sphere once again confirms that Ag2O is successfully loaded on the surface of WO3.
[0059] Figure 3 (a) is the TEM image of WO3 obtained in Example 2; Figure 3 (b) and Figure 3 (c) is a TEM image of the Ag2O / WO3 hollow microsphere composite material obtained in Example 2; Figure 3 (d) is the HRTEM image of the Ag2O / WO3 hollow microsphere composite material obtained in Example 2. Transmission electron microscopy (TEM) was used to further characterize the internal morphology of WO3 and Ag2O / WO3 materials. By comparing the bright field and dark field, it can be seen that hollow microsphere structures can be observed in WO3 and Ag2O / WO3, and Ag2O nanoparticles are well dispersed on the surface of WO3, which is basically consistent with the SEM observation results. Clear lattice fringes can be observed in the corresponding high-resolution transmission electron microscopy image of the Ag2O / WO3 material, and the lattice spacing is 0.365nm and 0.289nm, which match the (200) plane of WO3 and the (111) plane of Ag2O, respectively, proving the coexistence of Ag2O and WO3 and the successful construction of the pn heterojunction.
[0060] Application of the silver oxide / tungsten trioxide hollow microsphere composite material obtained in Example 2 as a hydrogen sulfide gas sensitive material:
[0061] (1) The resistance changes of WO3 and Ag2O / WO3 sensors when exposed to 10 ppm H2S gas at different operating temperatures were measured, and the gas-sensitive response performance of WO3 and Ag2O / WO3 sensors was evaluated to obtain the optimal operating temperature.
[0062] Figure 4 The response-temperature curves of WO3 and Ag2O / WO3 hollow microspheres obtained in Example 2 show that the response-temperature curves of WO3 and Ag2O / WO3 sensors show a "volcano-shaped" characteristic within the temperature range of 50-100°C, which can be explained by the surface resistance-controlled gas-sensitive mechanism of metal oxide semiconductor (SMO); the optimal operating temperature of the WO3 sensor is 70°C, and the response value to 10ppm H2S is 12.5; the response value of the Ag2O / WO3 sensor reaches the maximum at 60°C, and the response value to 10ppm H2S is as high as 207.12, which is about 16.5 times that of pure WO3.
[0063] (2) Investigate the response / recovery capabilities of WO3 and Ag2O / WO3 sensors to evaluate the real-time detection capability of the sensors for H2S gas.
[0064] Figure 5The response / recovery curves of WO3 and Ag2O / WO3 sensors to 10ppm H2S gas at the optimal working temperature (60℃ and 70℃) are shown. It can be seen that the response time of WO3 and Ag2O / WO3 sensors is 15s and 48s respectively. The Ag2O / WO3 composite sensor shows a faster response and a larger response amplitude, which proves its superior gas sensing performance. The enhanced response characteristics of the Ag2O / WO3 sensor may be due to the preferential reaction of H2S gas with the surface-loaded Ag2O NPs to generate Ag2S intermediates, which promotes the rapid response of the sensor. However, since the desorption ability of the sensitive material is weak at a lower working temperature, the recovery time is long at 60℃. In order to accelerate the desorption of H2S gas from the material surface, a pulse heating current needs to be provided outside the sensor. WO3 and Ag2O / WO3 are heated at 100℃ and 120℃ for 76s respectively.
[0065] (3) The continuous response of the Ag2O / WO3 sensor to H2S gas of different concentrations at the optimal working temperature was measured to obtain the dynamic sensing characteristic curve. The results are shown in Figure 6 .
[0066] from Figure 6 It can be seen that once the Ag2O / WO3 sensor is exposed to H2S gas, it can respond quickly and obviously, and as the H2S concentration increases, the response amplitude also increases. After the response is completed, the sensor is placed in the air, and the sensor sensitive material can quickly recover to stability under the assistance of pulse heating, which shows that the sensor has good reversibility; the detection limit is as low as 0.05ppm, and the response value is 1.77. This improvement in gas-sensing performance is due to its good hierarchical structure and the successful construction of pn heterojunction.
[0067] (4) The selectivity of WO3 and Ag2O / WO3 sensors was evaluated by measuring their responses to various interfering gases (e.g., ethanol, methanol, ethylene glycol, acetone, SO2, NO2, and CO). The results are shown in Figure 7 .
[0068] from Figure 7 It can be seen that compared with the WO3 sensor, the Ag2O / WO3 sensor has a higher selectivity for H2S gas, indicating that it has great application potential in complex gas environments. The improvement in the selectivity of the Ag2O / WO3 sensor can be attributed to the fact that Ag2O is easy to undergo sulfurization with H2S to generate highly conductive Ag2S, thereby promoting more gas molecules to react with the adsorbed surface oxygen, thereby greatly improving the selectivity of Ag2O for H2S.
[0069] (5) The short-term reproducibility and long-term stability of WO3 and Ag2O / WO3 sensors were evaluated. Figure 8.
[0070] Figure 8 (a) is the curve graph of 10 consecutive response / recovery experiments of the Ag2O / WO3 sensor exposed to 10 ppm H2S gas at 60°C on the 20th day. It can be seen that the Ag2O / WO3 sensor still exhibits good response / recovery performance at a lower operating temperature and has good short-term reproducibility. Figure 8 (b) shows the response values of WO3 and Ag2O / WO3 sensors and the change of resistance value (Ra) of Ag2O / WO3 sensors within 30 days. It can be seen that the drift of the response values of all sensors over time is small, and the overall baseline tends to be stable. The high stability of Ag2O / WO3 sensors can be attributed to the strong interaction between Ag2O and WO3 components, which is conducive to maintaining the structural integrity of the composite material and good gas sensing performance during long-term use.
[0071] The present invention synthesizes three-dimensional hierarchical hollow microsphere structure WO3 and Ag2O / WO3 heterojunction materials rich in oxygen vacancies and active sites by a two-step hydrothermal method. When the molar ratio of silver nitrate to tungsten hexachloride is 40%, the heterojunction sensor has the highest response value (S=207.12, 10ppm, 60°C) to H2S gas, which is about 16.5 times that of pure WO3, and its response time is 15s, and it can continuously detect H2S gas of different concentrations of 0.05-50ppm. In addition, the Ag2O / WO3 composite material has good reproducibility, long-term stability and high selectivity, and can effectively detect H2S gas under different relative humidity. The Ag2O / WO3 composite material has excellent gas-sensitive performance to low-concentration H2S, which is mainly attributed to its special microstructure, the formation of pn heterojunction and the sulfurization of Ag2O.
[0072] The most widely accepted sensing mechanism of metal oxide semiconductors is surface-controlled, which is based on the chemical adsorption of oxygen species (O 2- , O - 、O2 -The reaction between Ag2O / WO3 and the target gas causes a change in resistance, which is also a macroscopic expression of the sensor's sensitivity. Therefore, the morphology of the material is very important for the gas-sensing performance of the sensor. The improvement of the gas-sensing performance of Ag2O / WO3 is mainly due to the unique hierarchical structure of the composite material and the synergistic effect between the Ag2O and WO3 components. The characterization results show that WO3 and Ag2O / WO3 composite materials are three-dimensional hierarchical hollow microsphere structures self-assembled by nanoparticles. This structure not only increases the active sites on the surface of the material, but also provides more channels for gas transport, which is conducive to the improvement of gas-sensing performance. Ag grows on the surface of WO3 material in the form of Ag2O. The synergistic effect of Ag2O and WO3 components avoids the aggregation of Ag2O nanoparticles and enhances the roughness of the material surface.
[0073] (6) Study on the H2S gas sensing mechanism of Ag2O / WO3 sensor, the results are shown in Fig. 9 .
[0074] Fig. 9 (a) is a schematic diagram of the H2S gas sensing mechanism of the Ag2O / WO3 sensor. WO3 is an n-type semiconductor with free electrons as the main carriers, while Ag2O is a p-type semiconductor with holes as the main carriers. When the two materials are in contact with each other, since Ag2O is a narrow bandgap semiconductor (1.3eV) with a relatively low work function of 5.0eV, while WO3 is a relatively wide band semiconductor (2.6eV) with a higher work function of 5.24eV, this will cause electrons to transfer from Ag2O NPs to the n-type semiconductor WO3 to balance the Fermi level, forming a space charge region, that is, an electron depletion layer, thereby constructing a stable pn heterostructure. Before the sensor is exposed to H2S gas (60°C), the surface energy level generated by oxygen is lower than the Fermi level of the semiconductor, which will cause the oxygen molecules in the air to adsorb on the surface of the material and obtain electrons from the conduction band of the sensor material to form adsorbed oxygen molecules (O2 - ), the resistance increases, and the reaction equation is shown in the following equation (1):
[0075]
[0076] From equation (1), we can see that the increase in resistance of Ag2O / WO3 in air is due to the formation of a thick electron depletion layer (Ra = 55.3MΩ, S4). When the sensor is placed from air into a H2S gas environment, H2S reacts with oxygen ions on the surface of the material to generate SO2 and H2O, and releases electrons back to the conduction band, which in turn causes the resistance of Ag2O / WO3 to decrease (Rg = 0.267MΩ, S4). The reaction equation is shown in equation (2):
[0077]
[0078] However, in the H2S gas environment, due to the low Gibbs free energy of the reaction, Ag2O is easily converted into n-type Ag2S, which causes a change in the band structure and forms nn-type Ag2S-WO3, resulting in a significant reduction in resistance, such as Fig. 9 (b) is shown. Specifically, most of the holes in Ag2O are occupied by electrons in H2S molecules, thereby destroying the stability of the stable pn heterostructure. In order to maintain the hole-electron balance, a large number of trapped electrons are quickly released into WO3, and the resistance is reduced. In addition, by attaching and growing Ag2O nanoparticles on WO3 hollow microspheres to form a series of continuous npn junctions, the loss of electron current in WO3 hollow microspheres is prevented, which aggravates the reduction of WO3 conductivity. It can be measured that the resistance of the nanocomposite material is significantly reduced. The reaction formula is shown in the following formula (3):
[0079] Ag2O+H2S→Ag2S+H2O (3)
[0080] When the sensor is exposed to air again, for most H2S sensors based on Ag2O, since the desulfurization reaction of the formed Ag2S at room temperature is very slow, an external heating current is required to destroy the bonding between Ag2O and H2S gas, accelerate the oxidation of Ag2S to Ag2O, and desorb H2S gas from the surface of the material. The reaction equation is shown in the following equation (4). This sulfurization reaction and heating recovery improve the selectivity, sensitivity and excellent response / recovery performance of the sensor. This may be due to the fact that the hierarchical hollow microsphere heterogeneous structure is conducive to the diffusion / desorption of gas molecules. On the other hand, Ag2S converted from Ag2O nanoparticles has a smaller nanoparticle size, is highly active, and easily reacts with ambient oxygen under heating conditions.
[0081] Ag2S+O2→Ag2O+H2S (4).
Claims
1. A silver oxide / tungsten trioxide hollow microsphere composite material, characterized in that: The microscopic morphology of the silver oxide / tungsten trioxide hollow microsphere composite material is that silver grows on the surface of the tungsten trioxide hollow microsphere in the form of silver oxide nanoparticles, wherein: The silver oxide has a cubic crystal structure, the tungsten trioxide has a monoclinic crystal structure, and the interface region formed by the contact between the silver oxide and the tungsten trioxide is a pn heterojunction.
2. The material according to claim 1, characterized in that: The raw material required for preparing silver oxide is silver nitrate, and the raw material for preparing tungsten trioxide is tungsten hexachloride, wherein the molar ratio of silver nitrate to tungsten hexachloride is 30% to 50%.
3. A method for preparing a silver oxide / tungsten trioxide hollow microsphere composite material, characterized in that: Tungsten hexachloride is added to glacial acetic acid, stirred evenly and then subjected to hydrothermal reaction. After the reaction is completed, the mixture is cooled, washed by centrifugation, dried and then calcined to obtain tungsten trioxide solid powder. The tungsten trioxide powder obtained above is added to a mixed solution of anhydrous ethanol and deionized water, stirred evenly and then silver nitrate is added. The mixture is stirred evenly and then subjected to hydrothermal reaction. After the reaction is completed, the mixture is cooled, washed by centrifugation and dried to obtain a silver oxide / tungsten trioxide hollow microsphere composite material.
4. The method according to claim 3, characterized in that: The molar volume ratio of the tungsten hexachloride to the glacial acetic acid is 1 mmol:35 mL, and the mass volume ratio of the tungsten trioxide to the mixed solution of anhydrous ethanol and deionized water is 0.2 g:30 mL, wherein the volume ratio of the deionized water to anhydrous ethanol is 1:
1.
5. The method according to claim 3, characterized in that: The first hydrothermal reaction conditions are 170-190° C. for 11-13 h, and the second hydrothermal reaction conditions are 170-190° C. for 4-6 h.
6. The method according to claim 3, characterized in that: The drying conditions are all in a constant temperature vacuum drying oven at 60-70° C. for 8-12 hours, with the vacuum degree maintained at 700-800 Pa.
7. The method according to claim 3, characterized in that: The calcination conditions are calcination at 490-510° C. for 50-70 min, wherein the heating rate is 2° C. / min.
8. Use of the silver oxide / tungsten trioxide hollow microsphere composite material according to claim 1 or 2 as a hydrogen sulfide gas-sensitive material.
9. A bionic olfactory gas sensor, characterized in that: The hydrogen sulfide gas sensitive layer material of the sensor is the silver oxide / tungsten trioxide hollow microsphere composite material as claimed in claim 1 or 2.
10. The bionic olfactory gas sensor according to claim 9, characterized in that: The sensor can detect 0.05-50 ppm hydrogen sulfide gas in a continuous cycle at a low temperature of 60°C, with a sensitivity of 207.12 at 10 ppm, a response time of 15 s, and a detection limit of 50 ppb.